(untitled) (Asian Journal of Pharmaceutics (AJP), 2014)
The oral route is the easiest, cost effective, and most vital method for drug administration. Therefore, improvement of dosage forms mainly for the prolonged release purpose has been a challenge for scientists. Vesicular drug delivery systems are developed with a purpose to overcome problems coupled with the drugs such a poor bioavailability, protection from harsh gastric environment, and from gastric enzymes, which degrade the drug.Vesicular drug delivery systems such as liposomes, emulsions, niosomes, proniosomes, solid lipid-nano particles, ethosomes, nanoparticles, and pharmacosomes, etc have gained much attention, but emulsomes have rouse as system, which bypasses many disadvantages associated with other systems, developed as novel lipoidal vesicular system with internal solid fat core surrounded by phospholipid bilayer. This technology is designed to act as vehicle for poorly soluble drugs.The drug is enclosed in the emulsomes and provide prolong existence of drug in systemic circulation. Furthermore, emulsomal-based formulations of genetic drugs such as antisense oligonucleotides and plasmids for gene therapy that have clear potential for systemic utility are increasingly available. This review addresses the concept of emulsomal drug delivery system, summarizes the success of emulsomes for the delivery of small molecules, and special attention has been paid to its formulation design, advantages, biopharmaceutical aspects, stability aspects, and various aspects related to drug delivery including future aspects.